2011
DOI: 10.1016/j.econedurev.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Does schooling affect health behavior? Evidence from the educational expansion in Western Germany

Abstract: During the postwar period German states pursued policies to increase the share of young Germans obtaining a university entrance diploma (Abitur) by building more academic track schools, but the timing of educational expansion differed between states. This creates exogenous variation in the availability of higher education, which allows estimating the causal effect of education on health behaviors. Using the number of academic track schools in a state as an instrumental variable for years of schooling, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…In addition, our paper complements earlier work on the health effect of education in Western Germany, using the abolition of fees in academic track schools and academic track school constructions as different sources of exogenous variation in schooling (Jürges, Reinhold & Salm 2009). …”
Section: Introductionmentioning
confidence: 80%
“…In addition, our paper complements earlier work on the health effect of education in Western Germany, using the abolition of fees in academic track schools and academic track school constructions as different sources of exogenous variation in schooling (Jürges, Reinhold & Salm 2009). …”
Section: Introductionmentioning
confidence: 80%
“…However, James' effect sizes seem implausibly large (68% reduction in the probability to be obese for an extra year of schooling), and the effects in Kemptner et al are only present for men and not robust to including a higher-order polynomial in state-specific trends. Further, Jürges et al (2011) obtain a statistically significant result (at the 1% level)…”
mentioning
confidence: 85%
“…A similar conclusion is drawn by Li and Powdthavee (2015) for Australia, albeit using a smaller sample (N < 10, 000). 26 However, it seems that exposure to a completely different type of schooling (e.g., completing high school as in Kenkel et al 2006; college versus high-school as in Grimard and Parent, 2007;De Walque, 2007; or academic track versus regular track as in Jürges et al 2011) can lead to sizable reductions in smoking prevalence. This suggests that the schooling track and the associated peer group may be more important in smoking decisions than spending a certain number of years in secondary school.…”
mentioning
confidence: 99%
“…In line with this argument, previous studies have found education to positively influence health-related lifestyles and behaviors, such as smoking [36,38,40,64], drinking [36], or care seeking [53,56]. Despite this evidence, little is known about the actual mechanisms through which education affects behavioral patterns.…”
Section: Introductionmentioning
confidence: 98%